Kebiasaan Merokok dan Umur Terhadap Kejadian ISPA Pada Petani Di Kecamatan Ijen Bondowoso - Aditya Sapta Wardana; Isa Ma’rufi; Ristya Widi E Y (Pascasarjana Universitas Jember, 2020)
The number of Acute Respiratory Infection (ARI) among farmer showed high in area of Ijen – Bondowoso. There are several risk factors that may contribute of ARI case, such as individual factor, behavior, and environment. This study aims to analyze the correlation between smoking behavior and age toward acute respiratory syndrome among farmer. This was observational analytics, where the study design was cross sectional. The data was primer, where the information was collected from 101 farmer as respondent. This study was analyzed in SPSS 22.0. This study found that: 1) Age is correlated toward ARI case among farmer, and 2) smoking behavior also showed significant toward ARI case among farmer. Keyword: smoking behavior, age, acute respiratory infection